Language Skills in Business Context: A Bibliometric Analysis Using the VOS Viewer Application - Suprayogi, Yogi; Luckyardi, Senny; Kurnia, Dede; Khairusy, Mirza Abdi (Naifaderu Cipta Sejahtera, 2024)
Purpose The purpose of this study is to use VOSviewer to conduct a bibliometric examination of language skills in a business context. A quantitative description method is employed in this investigation. Methodology The data utilized in this study came from Google Scholar search results for the term